Konsep 5W+1H dalam Pendidikan (Komparasi Pemikirian Ki Hajar Dewantara dan K.H. A. Wahid Hasyim) - Supriyanti, Iin (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
Education is a conscious effort given by a person through a learning process to form a generation of character, knowledge and religion. Education itself is given by anyone who has more knowledge to humans who have not yet learned. With education it is expected to be able to increase the potential that exists in humans. Speaking of education, there are several figures who play a role in building, optimizing and shaping an education. By looking at the explanation above, the need for an understanding in society about education. In this article, we will discuss aspects of education in 5W + 1H. Namely What is the meaning of education? Who is the real educator? Why is education needed? When is education going on? Where is the education carried out? Abdul Wahid Hasyim was born on June 1, 1914 AD or to coincide with the 5th Wed 'al-awwal 1333 H in Jombang, East Java. He is the son of K.H Hasyim Asy'ari, founder of Nahdlatul Ulama. Ki Hadjar Dewantara was born in Yogyakarta on May 2, 1889. He was the fifth son of Soeryaningrat, the son of Paku Alam III. When he was born, he was given the name Soewardi Soeryaningrat, because he was still of royal descent, he was awarded the title Raden Mas (RM), which later became his full name Raden Mas Soewardi Soeryaningrat. What does education mean? From the two thoughts of the educational figure above, it can be concluded that education is a conscious effort made by someone in printing knowledgeable, character, and religious people. Who are the real educators? According to Ki Hajar Dewantara educating in the real sense is the process of humanizing humanity, namely the appointment of humans to the human level. Educating more liberates people from aspects of inner life (autonomy of thinking and making decisions, dignity, democratic mentality). According to K.H.A. Wahid Hasyim, an educator is not only competent in the field of science, but must master the science of religion. He was guided by the words of the Prophet Muhammad